On Fanaticism and Funding: Obeah Acts in Jamaican Moravian Missionary Communities - McGeary, Stephen A. (2022)
From the outset of the post-emancipation period in Jamaica, Moravian missionaries were forced to develop new and creative ways to acquire support for their evangelical efforts. Missionaries documented accounts of their interactions to rationalize their presence across the island and secure funds necessary to expand their outreach. During this period, Moravian missionary documents exhibited a stark increase in mentions of Obeah, a multifaceted Afro-Caribbean spiritual practice that held both restorative and destructive potential. Through an analysis of Moravian missionary documents coming out of Jamaica during the post-emancipation period, the author argues that Moravian missionaries portrayed Obeah as the antithesis to Moravian missionary work to justify their presence across Jamaica and, in turn, documented the forced confessions of Obeah practitioners to emphasize the power of their evangelical outreach for Moravian congregants and other potential supporters.
Keywords: post-Emancipation; Obeah; Jamaica; Missionary; Moravian